Removal of aspirin and paracetamol from aqueous solution by using tea waste modified PEI adsorbent - Hii, Kheng Wuong (2019)
The water bodies were determined to have been polluted by high concentration of pharmaceutical substances such as aspirin and paracetamol which may harm the ecosystem and bring health hazard to human. Conventional water treatment such as activated carbon used to remove these substances were not cost effective to be implemented. This study presented the alternative to the removal of aspirin and paracetamol from aqueous solution by using PEI modified tea waste adsorbent. The characteristics such as surface areas, pore volume and functional group of PEI-TW were identified by using Fourier Transform Infrared Spectroscopy (FTIR) and Brunauer-Emmett- Teller (BET). The total surface areas and pore volume of PEI-TW were 4.6748 m2/g and 0.0249 cm3/g, respectively. The highest removal percentage for aspirin was 87.34% in the optimum condition of initial concentration, dosage adsorbent; pH and temperature were 20 mg/L, 0.1g, pH 3 and temperature 60 ºC, respectively. Whereas removal of paracetamol achieved the percentage of 99.70% in the optimum condition of initial concentration, dosage adsorbent; pH and temperature were 20 mg/L, 0.1g, pH 7 and temperature 60 ºC, respectively. To describe the equilibrium isotherm for the adsorption of aspirin and paracetamol, the experimental data were fitted into Langmuir and Freundlich isotherm models, and both obeyed the Freundlich isotherm model with the correlation coefficient of 0.9865 and 0.9957 respectively. The adsorption process of aspirin and paracetamol obeyed the Pseudo-second order kinetic. The thermodynamic study indicated that the adsorption process of aspirin and paracetamol onto PEI modified tea waste adsorbent was feasible, spontaneous and endothermic. It can conclude that PEI modified tea waste adsorbent has high potential to be low-cost adsorbent and effective in the removal of paracetamol from aqueous solution compared to aspirin.